Effect of soybean meal replacement by slow-release urea on ruminal parameter, blood metabolites, and microbial protein synthesis in Zel ram - Zahra Alizadeh; Asadollah Teymouri Yansari; Yadollah Chashnidel; Mohammad Kazemifard; Samaneh Azarpajouh (Acta Scientiarum. Animal Sciences, 2020)
The objective of this study was to determine the effect of soybean meal replacement by slow-release urea on feed intake, ruminal parameters, blood metabolites, dry matter, nutrients digestion, and microbial protein synthesis (MPS) in ram. Rams were used for four 21-day periods. The experimental design was a 4×4 Latin square design. The experiment has consisted of the following four rations: 1) basic diet with soybean meal as a protein source, 2) basic diet with soybean meal plus 0.5 % of DM slow-release urea (SRU), 3) basic diet with soybean meal plus 1 % of DM SRU, and 4) basic diet with soybean meal plus 1.5 % of SRU, respectively. Soybean meal replacement by SRU decreased ruminal ammonia and blood urea. SRU increase in diets significantly increased acetic acid 3 hours after morning feeding, blood glucose, total purine, uric acid excretion, microbial nitrogen, and microbial protein. The results showed that soybean meal replacement by SRU sources had no negative effect on rams performance.